Hubungan Antara Kadar Gula Darah dengan Kejadian Inkontinensia Urin pada Lansia di Desa Tabanan, Bali - I Made Dwi Kurniawan; Ketut Suastika (Jurnal Sosial Teknologi, 2026)
Urinary incontinence is a common issue in the elderly, impacting their quality of life. One of the risk factors for its occurrence is blood sugar levels. This study aimed to determine the relationship between blood sugar levels and urinary incontinence in elderly individuals in Tabanan, Bali. A cross-sectional design was used, with simple random sampling. Interviews were conducted to gather demographic data and assess complaints of urinary incontinence, while blood tests were performed to measure blood sugar levels. The cut point for blood sugar was determined using the ROC curve. Chi-square bivariate analysis was performed to assess the relationship between blood sugar levels and urinary incontinence. The study involved 64 subjects, with 10 (15.6%) males and 54 (84.4%) females. Of the 39 subjects (60.9%) who reported urinary incontinence, 20 (51.3%) had blood sugar levels above the cut point, and 19 (48.7%) had levels below it. The results showed a statistically significant association (p = 0.048). In conclusion, blood sugar levels are associated with the incidence of urinary incontinence in the elderly.